2020
DOI: 10.1002/btpr.2980
|View full text |Cite
|
Sign up to set email alerts
|

The use of catechins in Chinese hamster ovary cell media for the improvement of monoclonal antibody yields and a reduction of acidic species

Abstract: Catechin compounds have potential benefits for recombinant monoclonal antibody (Mab) production as chemical additives in cell culture media. In this study, four catechin compounds catechin (Cat), epicatechin (EC), gallocatechin‐gallate (GCG), and epigallocatechin‐gallate (EGCG) were added to cell culture media (at 50 μM) and their effects on the recombinant Chinese hamster ovary (CHO) cell culture, specific productivity, and Mab quality were assessed. The results indicate that the improvement of specific produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Similar dependencies of effector levels on CHO growth were observed for catechins trapping cells in Sphase [48]. By analogy, treatment of cells with AMP is concentration-dependent and resulted in S-phase accumulation.…”
Section: Discussionsupporting
confidence: 65%
“…Similar dependencies of effector levels on CHO growth were observed for catechins trapping cells in Sphase [48]. By analogy, treatment of cells with AMP is concentration-dependent and resulted in S-phase accumulation.…”
Section: Discussionsupporting
confidence: 65%
“…The use of antioxidants in CHO cell cultures to improve monoclonal antibody production has been a topic of great interest [8,[33][34][35][36][37][38][39]. Nevertheless, the precise mechanisms by which RA impacts CHO cell growth, metabolism, and productivity need further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted recombinant proteins were quantified by ELISA. Cell concentrations were determined by direct cell counting with a Countess II FL counter to allow calculation of specific productivity, expressed as pg/cell/day, according to the following equation [30] :…”
Section: Evaluation Of Specific Productivitymentioning
confidence: 99%
“…Recombinant protein productivity is correlated to VCD and q p . [11,30] Here, we tested the cell cycle distribution of CHO cells using rylation is required for cells to exit G0 efficiently. [31] Via RT-qPCR (Figure 4E), it was found that the mRNA expression of CDK3 and Cyclin C decreased in CHO cells treated with apilimod.…”
Section: Effect Of Apilimod On Cell Cyclementioning
confidence: 99%